This preview shows page 1. Sign up to view the full content.
Unformatted text preview: 2 x dx = e 1 2 log x = x 1 2 : x 1 2 dy dx + 1 2 x1 2 y = 1 2 x3 2 d dx ( yx 1 2 ) = 1 2 x3 2 yx 1 2 =x1 2 + C y =1 x + Cx1 2 Using the initial condition y (1) = 4, we get that 4 =1 + C (1). Hence C = 5 and y ( x ) =1 x + 5 x1 2 . 1...
View
Full
Document
This note was uploaded on 04/02/2008 for the course MATH 33B taught by Professor Staff during the Spring '07 term at UCLA.
 Spring '07
 staff
 Math

Click to edit the document details